2022
DOI: 10.5296/ije.v14i1.19507
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Vocational Teaching and Learning: Perception and Readiness among Lecturers

Abstract: Sustainable economic growth and socioeconomic stability can be achieved through technical and vocational education (TVET). Improving TVET education can help empower students to play a significant role in achieving sustainable growth in their country. Teaching and learning in TVET institutions need to be reformed to achieve the international standard and increase students' understanding and motivation. Recently, gamification appears to be an emerging trend in education due to its conviction that it can support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Previous research on gamification only focused on using gamification to increase student motivation [38][39][40], foster student learning outcomes [41] [42], communication and collaboration skills [43], routine problem solving [44], participation and a learning experience [45], and improve academic performance [40]. Existing educational games usually have character selection, conflicts or problems that must be solved to level up, material content, and strategies used to complete the game according to needs [46], specifically designed for the development of problem-solving skills [47] [48].…”
Section: Gamificationmentioning
confidence: 99%
“…Previous research on gamification only focused on using gamification to increase student motivation [38][39][40], foster student learning outcomes [41] [42], communication and collaboration skills [43], routine problem solving [44], participation and a learning experience [45], and improve academic performance [40]. Existing educational games usually have character selection, conflicts or problems that must be solved to level up, material content, and strategies used to complete the game according to needs [46], specifically designed for the development of problem-solving skills [47] [48].…”
Section: Gamificationmentioning
confidence: 99%
“…It focuses on students who wish to follow maritime professions and have chosen the respective Sector in the Greek Vocational High School. Through this gamified environment, the students will be introduced to the history of seamanship, not by applying traditional methods of teaching that tend to be more theoretical and less appealing to students who do not have a strong background in history, since the last time these students were taught history would have been in the Lower Secondary School (Gymnasium) 1 . 2 The application of gamification in the past decade has seen a significant increase and has produced positive results.…”
Section: Technical Curriculum Of Vocational and Educationalmentioning
confidence: 99%
“…The concept of gamification emerged just before 2010 [5] and has since been applied in many sectors of our lives including education. Gamification is the application of game-design elements to non-game contexts, thus allowing learners to improve their knowledge of a subject through games; thus, a serious process, such as teaching, is transformed by adding entertaining elements [1], [6]. Extensive research on gamification has shown that it has serious benefits for students of all educational sectors, including VET, where the main focus is primarily on practical training and skills-based learning [2] and teaching methods aim at mastery over competency since the graduates are expected to assist, as future professionals and parts of each country's workforce, in achieving sustainable economic growth and socio-economic stability [1].…”
Section: Gamification In Vocational Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in motivation is frequently ascribed to the intrinsic pleasure and feeling of accomplishment that students obtain from gamified educational experiences. Gamification has emerged as a potent strategy to tackle the persistent problem of student disengagement, which can impede the efficacy of traditional instructional methods (Ensmann & Whiteside, 2022;Omar et al, 2022;Pendy, 2023).…”
Section: Introductionmentioning
confidence: 99%